Ofício do assistente substituto do magistrado do distrito de Xiangshan, Gu, ao procurador de Macau, sobre os cinco franceses que tinham sido raptados pelos navios ingleses, em Java, e que apanharam um navio de mercadoria inglês que os trouxe de Batávia a Macau (1745)
This archival document is a Qing-dynasty official warrant (*yìn xìn pái*) issued on the ninth day of the seventh lunar month in the tenth year of the Qianlong reign (1745) by the *Hǎifáng Jūnmín Fǔ* (Maritime Defence Prefecture for Military and Civil Affairs), directing the *Yí Mù*—the Portuguese *capitão-mor* of Macau acting as the Qing-appointed ‘Foreign Headman’—to investigate matters concerning Dutch and British maritime activity in the Pearl River Delta. The warrant responds to a memorial from the Assistant Magistrate (*xiàn chéng*) of Xiangshan County, reporting that five individuals, including *Wèi Zhā Nān Ài*, claimed to have been seized by British ships en route from Guangzhou to Batavia in the preceding year and taken to Britain (*Bā Guó*), yet were now travelling again aboard a British vessel to Macau; it further notes the unexplained continued residence in Macau of Dutch chief merchant (*dà bān*) *Wù Lóu Lǐ*, who had petitioned for a travel permit to Macau but failed to repatriate to the Netherlands (*Fú Lán Xī*). The directive requires verification of the five men’s Dutch nationality, the factual accuracy of their seizure narrative, the circumstances of their re-embarkation with British merchant *Hā Kā*, and the reasons for *Wù Lóu Lǐ*’s prolonged stay. The document originates from Xiangshan County, concerns Macau and Guangdong-Fujian maritime routes, and reflects Qing administrative protocols under the Canton System, including inter-imperial commercial surveillance and jurisdictional oversight of foreign merchants.
Keywords: Batavia; British maritime activity; Dutch maritime activity; Foreign Headman; Guangzhou; Macau–Qing relations; Maritime Defence Prefecture for Military and Civil Affairs; Pearl River Delta; Portuguese capitão-mor of Macau; Qing Dynasty official warrant; Sino-Portuguese jurisdiction; Transcription; Wei Zhao Nan Ai; Wu Lou Li